The IAGOS-CORE aerosol package: instrument design, operation and performance for continuous measurement aboard in-service aircraft - Ulrich Bundke; Marcel Berg; Norbert Houben; Amir Ibrahim; Markus Fiebig; Frank Tettich; Christoph Klaus; Harald Franke; Andreas Petzold (Tellus: Series B, Chemical and Physical Meteorology, 2015)
This work presents the characterisation of the Aerosol Package for the European Research Infrastructure IAGOS (In-service Aircraft for a Global Observing System). Condensation particle counter (CPC) are used to measure the aerosol number concentration of the total and the non-volatile particles. The size distribution is measured by means of an optical particle counter (OPC) in the diameter range of 0.25–3 µm. In particular the OPC is characterised for (1) leakage, (2) flow and calibration stability over the expected IAGOS pressure range of 170 hPa to 1013 hPa, (3) OPC accuracy test by comparing extinction measurements with calculated values from Mie theory using the OPC size distribution and (4) the inter-instrumental precision. The CPC is characterised in the same pressure range for (1) the lower cut-off diameter, (2) the instrument accuracy by comparing with a reference instrument (Faraday Cup Electrometer, FCE) and (3) the instrument precision. We conclude that the IAGOS Aerosol Package is a fully automated, robust, low-maintenance instrument providing high precision measurements with good accuracy.